PEMANFAATAN KEMANGI LOKAL JENIS KANDANGU MBUKU SEBAGAI BAHAN PENGAWET ALAMI DALAM PENGOLAHAN PENYEDAP RASA NON MSG: Utilization of Local Basil ”Kandangu Mbuku” As A Natural Preservative In The Processing Of Non-MSG Flavor Enhancer - Maria Anjelina Taka; Yessy Tamu Ina (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2026)
This study aimed to produce a natural non-MSG flavor enhancer made from local kandangu mbuku basil extract and to analyze its chemical characteristics, including moisture content, pH, and total protein, as well as its organoleptic properties such as color, taste, texture, and panelists’ preference level. The study employed a Completely Randomized Design (CRD) with different concentrations of kandangu mbuku basil extract in the non-MSG flavoring formulation. The treatments consisted of four concentration levels: P0 = 0%, P1 = 30%, P2 = 35%, and P3 = 40%, with a total of 20 sample units. The observed variables included moisture content, pH, total protein, and organoleptic parameters covering color, taste, texture, and panelists’ preference. The data were analyzed using analysis of variance (ANOVA) and non-parametric tests. The results showed that the addition of kandangu mbuku basil extract had a significant effect on the pH value of the product. Organoleptically, the 35% concentration treatment produced the best results for color and panelists’ preference, while the 40% concentration resulted in the highest taste score. Based on these findings, the 35% concentration was considered the most optimal formulation for producing a natural non-MSG flavor enhancer based on kandangu mbuku basil. Keywords: chicken meat, basil extract, kandangu mbuku, organoleptic, moisture content.